Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend - Pamplona, Denise; Nihei, Silvio S.; Couri, Márcia S.; Pont, Adrian C. (Zootaxa, 2016)
The subgenera Morellia Robineau-Desvoidy, 1830 and Parapyrellia Townsend, 1915 of Morellia (Diptera, Muscidae) are revised. Forty-two species of the subgenus Morellia (out of 50) and seven of the subgenus Parapyrellia (all species) are redescribed and illustrated, and 48 species are keyed (41 spp. of Morellia and 7 spp. of Parapyrellia). Morellia (M.) cashmirana van Emden, 1965, originally described as a subspecies of M. (M.) hortorum (Fallén, 1817), is raised to species rank, stat. nov. Four species are transferred from the subgenus Morellia to the subgenus Parapyrellia (subgen. comb. nov.): M. dendropanacis Pamplona & Couri, 1995; M. lopesae Pamplona, 1986; M. roppai Pamplona, 1986 and M. semimarginata (Stein, 1918).